Lichen planus pigmentosus and frontal fibrosing alopecia: The link explored - Ashraf Raihan; Muthu Sendhil Kumaran (Wolters Kluwer Medknow Publications, 2018)
There has been a recent rush of data regarding the combined presentation of lichen planus pigmentosus and frontal fibrosing alopecia in premenoposal women of dark skin. This review article addresses the relationship between the two.